2017
DOI: 10.14740/jh336w
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Memory B Lymphocytes in Children With Newly Diagnosed Immune Thrombocytopenia

Abstract: Background: Immune (idiopathic) thrombocytopenic purpura (ITP) is a primary autoimmune disease. It is characterized by a diminished peripheral platelet count (< 100 × 10 9 /L) caused by platelet destruction with an increased risk of mucocutaneous bleeding. The diagnosis of ITP depends on clinical characteristics and the laboratory examinations conducted, as well as the ability to exclude other diseases associated with thrombocytopenia. Antiplatelet autoantibodies are responsible for platelet destruction and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
5
9
1
Order By: Relevance
“…According to TLCs, the present study was in agreement with those of Khalifa et al [8] [2], who also reported no statistically significant difference between ITP patients and controls. However, Fahim and Monir [10] found that the TLC count was significantly higher in ITP patients than in controls; this may have been because of neutrophilia or lymphocytosis that may accompany the disease..…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to TLCs, the present study was in agreement with those of Khalifa et al [8] [2], who also reported no statistically significant difference between ITP patients and controls. However, Fahim and Monir [10] found that the TLC count was significantly higher in ITP patients than in controls; this may have been because of neutrophilia or lymphocytosis that may accompany the disease..…”
Section: Discussionsupporting
confidence: 93%
“…There was no statistically significant differences among studied and control groups regarding hemoglobin level and total leucocyte count , while platelets was significantly lower in patients group compared to control group Table (1) There were one patient (5.0% ) were asymptomatic at diagnosis , five patients (25.0%) were presented with preceding febrile illness ,nineteen patients(95.0%) had skin manifestation, four patients (20%) had bleeding tendency and non of patients had organomegaly (Table (2).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with numerous previous studies that stated the upregulation of B cells in ITP. 11,14,19,20 B cells are the principal creators of antiplatelet antibodies. These cells proliferate into autoantibody-secreting cells under the effects of platelet-specific helper T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors aimed to investigate the linkage between Bregs and immune thrombocytopenic purpura (ITP) in children. They revealed a decreased number of Bregs in the peripheral blood in patients with ITP [25].…”
Section: Introductionmentioning
confidence: 96%